Boost converter with power factor correction - Kamarudin, Kamry (2012)
The boost converter is a type of the switched mode power supply which normally to step up the voltage since the voltage output is large than the input voltage. A simple boost converter consists of at least two switching components such as diode and transistor with combine to an energy storage element which is capacitor. As a DC to DC converter, the input of the converter must be a direct voltage and the output with also in range of direct voltage with higher than the voltage input and the switching component control the operation of the converter with the capacitor as the energy storage and the dded component is used for filtering purpose. The objective of this project mainly to feed the load of inverter for 3-phase AC motors which is for 300W application and able to supplied the constant voltage output from an AC input voltage. As the scope of this project, the chapter covered as much as to design a boost converter which has power factor correction to be feed on the 3-phase inverted.